Measurement of Compound Sound Sources with Adaptive Spatial Radiation for Low-Frequency Active Noise Control Applications - GIOUVANAKIS, Marios; SEVASTIADIS, Christos; PAPANIKOLAOU, George (Archives of Acoustics, 2021)
The proposed compound sound sources for low-frequency noise control applications are composed of dipole sources. Their spatial radiation, which is critical in the modal field of small, closed spaces, is intended to be controlled with independent driving signals of each dipole. The need for small and efficient low-frequency elementary monopole sources led to the proposed vented sub-woofer loudspeaker design with low force factor (low-Bl) drivers. The investigated sources are set up in quadrupole configurations and measured in terms of polar near field response patterns to verify the theoretical predictions. The measurement results consist of the validation of the proposed compound sound sources on the implementation of active noise control problems in the low-frequency range. Also, their small size and modular construction make them interesting for use in other applications.